Quantitative study of lung structure in COPD patients based on low-dose Karl iterative reconstruction - Ye, Yizhai; Li, Juehui; Wang, Weigen; He, Jianhua; Yang, Qi (Vojnosanitetski pregled, 2025)
Background/Aim. Low-dose Karl iterative reconstruction (KIR) is a commonly used technique in medical imaging. An iterative algorithm reduces the dose of X-ray radiation while ensuring image quality, making it a safer and more convenient imaging method. The aim of the study was to analyze the assessment value of low-dose KIR for the lung structure of patients with chronic obstructive pulmonary disease (COPD). Methods. The study included a total of 135 COPD patients undergoing bronchoscopic biopsy from August 2022 to July 2023. Low-dose KIR was conducted. Two groups were formed according to the lung structure examined by bronchoscopic biopsy: an airway remodeling group and a non-airway remodeling group. The examination indicators of low-dose KIR were compared. Receiver operating characteristic curves were plotted to analyze the clinical value of low-dose KIR for assessing the lung structure. Results. According to the examination results of chest X-ray, airway remodeling was done in 85 out of 135 (62.96%) COPD patients. The sensitivities, specificities, and areas under the curves of computed tomography value, noise value, signal-to-noise ratio, and contrast-to-noise ratio were 0.976 vs. 0.965 vs. 0.953 vs. 0.980, 0.960 vs. 0.940 vs. 0.927 vs. 0.753, and 0.623 vs. 0.643 vs. 0.670 vs. 0.640, respectively. Conclusion. Low-dose KIR proved to be a very accurate and fast method for the quantitative study of lung structure in COPD patients.